Hydrological Analysis and Assessment about the impact of Limestone Mining on water Pollution in Hial Area , Bolangir district, Odisha, India - B.K. Ratha, S.R. Barick (International Journal of Scientific Research and Management (IJSRM), 2017)
80 percent area of Odisha are underlain by hard rock .Therefore Ground water resource is very scarce inmost part of the state. Bolangir district is known as drought prone area .Our study area comes under drought prone zone. Most people depend on ground water for agricultural and drinking purpose. Water is a scarcere source there. A number of Lime Stone mines are being operated in the study area adds to further scarcity as contamination may render a part of available resource as unsuitable for use . Lithology controls the water chemistry of the area . There is a direct relationship between the rock type and water composition of the area. Rock type is the main factor which is responsible for controlling water quality mechanism of the study area. While Lime Stone affects the water pollution , simultaneously host rock in the area and variation of the rock type is also notable factor in its hydrology. Therefore it is essential to make a detailed hydrological study of the area under observation in order to assess the impact of Lime Stone Mining on water pollution .For quality evaluation during pre monsoon period and post monsoon period from 2010 to 2015 water samples were collected from the study area and were analysed in Laboratory .